The Role of Circular Economy in Transforming Manufacturing Workplace Towards Net Zero Emissions - Afsa Parveen; Nishu Saini; Seema Rani (The International Journal of Education Management and Sociology, 2025)
The manufacturing sector is a primary contributor to global environmental issues, such as waste production, resource depletion, and greenhouse gas (GHG) emissions. As industries face increasing pressure to align with net zero emission targets, one revolutionary approach to tackling these environmental issues is circular economy. Unlike the traditional linear "take-make-dispose" approach, the CE emphasizes closing material loops through strategies as product life extension, recycling, and remanufacturing, which lower waste and pollution. The current study explores the dual the circular economy's contribution to improving environmental sustainability and changing manufacturing environments focusing on its potential to drive net zero emissions while transforming organizational structures, employee roles and workplace culture. The existing research adopts a qualitative research methodology, leveraging secondary data from industry reports, case studies, and peer-reviewed journals to analyse the application, difficulties, and effects of CE practices in the manufacturing sector. After reviewing the literature, the research findings revealed that CE adoption is gaining momentum globally, with companies integrating strategies like resource-efficient production, closed-loop supply chains and renewable energy use.